THE ROLE OF SELF-COMPASSION ON STUDENT ENGAGEMENT AMONG UNIVERSITY STUDENTS: A SYSTEMATIC LITERATURE REVIEW - Bella Gemilang Putri; Bambang Suryadi (Yayasan Adra Karima Hubbi, 2026)
Student engagement is a crucial factor in academic success, as it reflects students’ behavioral, emotional, and cognitive involvement in the learning process. However, academic demands often lead to stress, anxiety, and burnout, which may reduce students’ engagement. One psychological factor that has the potential to enhance student engagement is self-compassion, defined as the ability to treat oneself with kindness, recognize failure as part of the shared human experience, and maintain balanced awareness of personal difficulties. This study aims to systematically review the role of self-compassion in student engagement among university students. A Systematic Literature Review (SLR) approach was employed following the PRISMA 2020 guidelines. Data were collected from the Scopus and Taylor & Francis databases using the keywords “self-compassion,” “student engagement,” and “higher education.” Of the 46 articles initially identified, 18 met the inclusion criteria and were included in the analysis. The findings indicate that self-compassion positively contributes to psychological well-being, emotion regulation, resilience, and academic motivation while reducing burnout, anxiety, and fear of failure. Furthermore, self-compassion was found to function as both a mediator and a moderator in the relationship between various psychological factors and student engagement. These findings suggest that self-compassion serves as an important psychological resource that supports students’ academic involvement. Therefore, integrating self-compassion development into counseling services, character-building programs, and technology-based interventions may represent an effective strategy for enhancing student engagement in higher education.